Relationship between family support and quality of life of breast cancer patients undergoing chemotherapy at Santa Elisabeth Hospital - Lubis, Ronauli Agustina; Sinurat, Samfriati; Perangin-Angin, Indra Hizkia (Jurnal Keperawatan, 2023)
Introduction: The decline in the quality of life of breast cancer patients undergoing chemotherapy causes suffering, and the suffering experienced by chemotherapy can be a decrease in the ability to think, remember and concentrate. Generally, breast cancer patients undergoing chemotherapy will experience anxiety and fear of the possibility of death, and in the end, they lose their autonomy, reduce self-esteem, and lose hope, indicating that there is no meaning in life. Therefore, people with breast cancer undergoing chemotherapy need strong companions from the surrounding environment, especially their family support through supportive attitudes, actions, and acceptance, and are always ready to provide help and assistance. Objectives:   To determine the relationship between family support and quality of life of breast cancer patients undergoing chemotherapy. Methods:  This study was a non-experimental - a correlational research design with a Cross-Sectional approach. Results: The results of the study conducted by the researcher showed that the presence of family support could improve the patient's quality of life. Conclusions: The quality of life of breast cancer patients undergoing chemotherapy is getting more optimal. Researchers hope to improve the quality of life for breast cancer patients undergoing chemotherapy by providing positive support such as sincere care and affection, the motivation that builds the patient's spirit.